Generative component-based IP camera design - Garcia, Paulo (2013)
The developers' need for shorter time to market and the increasing complexity of electronic systems caused by the demand for a myriad of functional and non-functional characteristics, led to the adoption of novel design and implementation techniques to bridge the concept to implementation gap. This paper presents model-driven generative design in the implementation of IP cameras for integration on Home Appliance Networks. The refinement process for the Product Family is depicted for two camera configurations and the use of generative design for implementing the models is described, displaying the variability in terms of features and implementation. The topology is also described to show how architectural models can be used to aid the process and ensure ease of integration and interoperability between functionalities, regardless of their implementation (gateware, software or hybrid).